Taxation and Labour Supply: Evidence from a Representative Population Survey - Bernd Hayo; Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
We study the influence of taxation on labour supply using a specifically designed representative survey of the German population. First, we investigate whether taxes generally matter for the labour supply decisions of our respondents. Around 41 per cent report taking taxes into consideration, which implies that the majority of the German population appears unresponsive to taxation. Second, we look at self-reported labour supply adjustments following a recently enacted payroll tax change. Only around 12 per cent of all respondents report an actual labour supply response, but we find evidence of an income, as well as a substitution, effect of the tax change. Our conclusion is that effects of taxes on labour supply in Germany are likely small. We analyse the correlation with economic and socio-demographic variables, and find that the self-employed are relatively more sensitive to taxation and that low interest rates reduce incentives for an expansion of the labour supply.
Keywords: E62; H30; J22; 330; Taxation; Labour supply; Representative population survey Germany